The geology and geochemistry of the Sterkspruit intrusion, Barberton Mountain Land, Mpumalanga province. - Conway, Gavin Patrick. (My University, 1997)
The Sterkspruit Intrusion, in the south-western portion of the Barberton greenstone belt, is a sill-like body containing rocks of gabbroic to dioritic composition, It is hosted by a sequence of komatilitic basalts and komatilites of the Lower Onverwacht Group. The intrusion is considered unique in this area in that it lacks ultramafic components and has no affinities with the surrounding mafic- to- ultramafic lavas, The gabbroic suite also contains an unusual abundance of quartz, and the chill margin shows an evolved quartz-normative, tholelitic parental magma. ( Abbreviation abstract )
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science.
Keywords: Geology -- South Africa -- Barberton.; Geochemistry -- South Africa -- Barberton.